PENGGUNAAN MEDIA SOSIAL DAN CARA BELAJAR SISWA SMP TELEKOMUNIKASI PEKANBARU - Hafeli, Ancha Reka; Umari, Tri; Yakub, Elni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : One of the technological facilities that serve as â€œfleshâ€ of society is a social networking site. In the daily practice, such social networking services routinely accessed by hundreds of thousands or even millions of internet users from all over the world. It is Often found that many students use social media until they forget the time. This will have an effect on the way of student learning. Therefore, the researchers feel that it needs to determine the use of social media and the way of studentâ€™s learning. The aim of this research is to know the general description of social media usege among students and to know how they learn in terms of the use of social media. The population and sample in this research are 111 students who use social media. This research uses quantitative descriptive method. Data collection techniques is using questionnaires. To analyze data using percentage technique. The results of this research is that the students in the social media access is in the low category in a range of < 2 hours. Social media that is often used by students is Facebook continued by WhatsApp, Istagram and the most frequently accessed is Facebook. Students using social media at free time, before sleep and while learning. Students who use social media are a good enough in learning. It willl be good for student,in order to maintain the use social media,to manage the time for social media and studying and be wiser in using social media and improve the way how to learn effective and efficient learning. For parents and teachers, it needs to pay more attention to the usege of social media and students learning.Keywords : Social Media, Student Learning